Surgical results and factors affecting outcome in adult patients with sensory exotropia - Jung, Eun Hye (Eye (Lond), 2018)
PURPOSE: To report the results of surgical treatment for sensory exotropia and to examine the factors associated with the surgical outcome. METHODS: The records of patients with sensory exotropia who were older than 18 years at the time of surgery and were followed up for at least 1 year postoperatively were retrospectively reviewed. Patients with visual acuity of ≤20/100 in the amblyopic eye were enrolled. Surgical success was defined as a final deviation of <10 prism diopters (PD) at distance in the primary position. Preoperative patient characteristics, surgical procedures performed, and early postoperative ocular alignment were evaluated as potential factors associated with the surgical outcome. RESULTS: A total of 64 patients were included, of whom 40 (62.5%) achieved surgical success, four (6.3%) showed overcorrection, and 20 (31.3%) experienced recurrence over an average follow-up duration of 2.0 ± 1.2 years. Preoperative distant and near angles of deviation were significant factors associated with surgical outcome. Regardless of the high rate of recurrence, initial postoperative large overcorrection did not guarantee a positive result. Instead, presence of initial postoperative esodrift was related to surgical success. Multivariable analysis revealed that only the preoperative distant angle of deviation was significantly associated with surgical outcome. CONCLUSION: The long-term outcome of surgery for sensory exotropia was satisfactory, and patients with small preoperative distant angle of exodeviation showed more favorable outcome.